Safety of Cyproheptadine, an Orexigenic Drug. Analysis of the French National Pharmacovigilance Data-Base and Systematic Review - Bertrand, Valérie; Massy, Nathalie; Vegas, Nancy; Gras, Valérie; Chalouhi, Christel; Tavolacci, Marie-Pierre; Abadie, Véronique (Frontiers in Pediatrics, 2021)
Objectives: Cyproheptadine is a first-generation H1-antihistamine drug first that was distributed in the 1960s. While its orexigenic effect was observed early, cyprohepatdine is not yet authorized for this indication in all countries today. There is an increasing medical interest and demand for the orexigenic effect of cryoheptadine, especially in children with poor appetite. As cyprohepatdine might be evaluated in future clinical trials, we wanted to assess its safety profile. Methods: Using the French national pharmacovigilance database, we retrospectively analysed all pediatric and adult reports of adverse effects of cyprohepatdine recorded since its first distribution in France. Next, we performed a systematic review of the literature of cyprohepatdine adverse effects. Results: Since 1985, 93 adverse effects were reported in the French pharmacovigilance database (adults 81.7%, children 18.3%); these were mainly neurological symptoms (n=38, adults 71%, children 28.9%), and hepatic complications (n=15, adults 86.7%, children 13.3%). In the literature, the most frequent adverse effect reported was drowsiness in adults or children, and five case reports noted liver complications in adults. We estimated the frequency of hepatic adverse effects at 0.27 to 1.4/1000, regardless of age. Conclusion: Cyprohepatdine can be considered a safe drug. Mild neurological effects appear to be frequent, and hepatotoxicity is uncommon to rare. Randomized controlled trials are needed to evaluate the safety and efficacy of cyprohepatidine before authorization for appetite stimulation, especially in young children as studies at this age are lacking. Possible hepatic complications should be monitored, as very rare cases of liver failure have been reported.